Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 78709 by jagoll last updated on 20/Jan/20

if sin^2 x+sin x = 1  what is cos^(12) x+3cos^(10) x+3cos^8 x+cos^6 x

$$\mathrm{if}\:\mathrm{sin}\:^{\mathrm{2}} \mathrm{x}+\mathrm{sin}\:\mathrm{x}\:=\:\mathrm{1} \\ $$$$\mathrm{what}\:\mathrm{is}\:\mathrm{cos}\:^{\mathrm{12}} \mathrm{x}+\mathrm{3cos}\:^{\mathrm{10}} \mathrm{x}+\mathrm{3cos}\:^{\mathrm{8}} \mathrm{x}+\mathrm{cos}\:^{\mathrm{6}} \mathrm{x} \\ $$

Commented by jagoll last updated on 20/Jan/20

thanks sir john and sir som

$$\mathrm{thanks}\:\mathrm{sir}\:\mathrm{john}\:\mathrm{and}\:\mathrm{sir}\:\mathrm{som} \\ $$

Answered by john santu last updated on 20/Jan/20

Commented by john santu last updated on 20/Jan/20

edit : cos^6 x=(((3−(√5))/2))×((((√5)−1)/2))=(√5)−2  ∴ ((√5)−2){(√5)−2+((9−3(√5)+3(√5)−3)/2)+1}=  ((√5)−2)((√5)−1+(6/2)) =   ((√5)−2)((√5)+2)=5−4 =1 ★

$${edit}\::\:\mathrm{cos}\:^{\mathrm{6}} {x}=\left(\frac{\mathrm{3}−\sqrt{\mathrm{5}}}{\mathrm{2}}\right)×\left(\frac{\sqrt{\mathrm{5}}−\mathrm{1}}{\mathrm{2}}\right)=\sqrt{\mathrm{5}}−\mathrm{2} \\ $$$$\therefore\:\left(\sqrt{\mathrm{5}}−\mathrm{2}\right)\left\{\sqrt{\mathrm{5}}−\mathrm{2}+\frac{\mathrm{9}−\mathrm{3}\sqrt{\mathrm{5}}+\mathrm{3}\sqrt{\mathrm{5}}−\mathrm{3}}{\mathrm{2}}+\mathrm{1}\right\}= \\ $$$$\left(\sqrt{\mathrm{5}}−\mathrm{2}\right)\left(\sqrt{\mathrm{5}}−\mathrm{1}+\frac{\mathrm{6}}{\mathrm{2}}\right)\:=\: \\ $$$$\left(\sqrt{\mathrm{5}}−\mathrm{2}\right)\left(\sqrt{\mathrm{5}}+\mathrm{2}\right)=\mathrm{5}−\mathrm{4}\:=\mathrm{1}\:\bigstar \\ $$

Answered by som(math1967) last updated on 20/Jan/20

sin^2 x+sinx=1  sinx=1−sin^2 x=cos^2 x  ∴sin^2 x=cos^4 x  Now cos^(12) x+3cos^(10) x+3cos^8 x+cos^6 x  =(cos^4 x)^3 +3cos^4 x.cos^2 x(cos^4 x+cos^2 x)                                                       +(cos^2 x)^3   =(cos^4 x+cos^2 x)^3   =(sin^2 x+cos^2 x)^3 =1^3 =1ans ★  ★cos^4 x=sin^2 x from condition

$${sin}^{\mathrm{2}} {x}+{sinx}=\mathrm{1} \\ $$$${sinx}=\mathrm{1}−{sin}^{\mathrm{2}} {x}={cos}^{\mathrm{2}} {x} \\ $$$$\therefore{sin}^{\mathrm{2}} {x}={cos}^{\mathrm{4}} {x} \\ $$$${Now}\:{cos}^{\mathrm{12}} {x}+\mathrm{3}{cos}^{\mathrm{10}} {x}+\mathrm{3}{cos}^{\mathrm{8}} {x}+{cos}^{\mathrm{6}} {x} \\ $$$$=\left({cos}^{\mathrm{4}} {x}\right)^{\mathrm{3}} +\mathrm{3}{cos}^{\mathrm{4}} {x}.{cos}^{\mathrm{2}} {x}\left({cos}^{\mathrm{4}} {x}+{cos}^{\mathrm{2}} {x}\right) \\ $$$$\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:+\left({cos}^{\mathrm{2}} {x}\right)^{\mathrm{3}} \\ $$$$=\left({cos}^{\mathrm{4}} {x}+{cos}^{\mathrm{2}} {x}\right)^{\mathrm{3}} \\ $$$$=\left({sin}^{\mathrm{2}} {x}+{cos}^{\mathrm{2}} {x}\right)^{\mathrm{3}} =\mathrm{1}^{\mathrm{3}} =\mathrm{1}{ans}\:\bigstar \\ $$$$\bigstar{cos}^{\mathrm{4}} {x}={sin}^{\mathrm{2}} {x}\:{from}\:{condition} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com